2016
DOI: 10.1002/2016gl070255
|View full text |Cite
|
Sign up to set email alerts
|

On the role of extratropical air‐sea interaction in the persistence of the Southern Annular Mode

Abstract: Using the daily atmosphere and ocean reanalysis data, this study highlights the role of extratropical air‐sea interaction in the variability of the Southern Annular Mode (SAM). Our analysis shows that the SAM‐induced meridional dipolar sea surface temperature (SST) anomalies, through surface heat fluxes, can maintain persistent lower tropospheric temperature anomalies, which further results in anomalous eddy momentum forcing enhancing the persistence of the SAM. With the Finite Amplitude Wave Activity diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Many studies have suggested that the Arctic warming can induce AO‐like atmospheric response (e.g., Butler et al, ; Nie et al, ). Variations of AO and WP are closely related to the change of sea ice (e.g., Linkin & Nigam, ; Overland et al, ) as well as the SST anomalies in extratropical and tropical oceans (e.g., Kwon et al, ; Xiao et al, ). The latter is suggested influence the TP snowfall by modulating the moisture supply as well (Yuan et al, , ).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have suggested that the Arctic warming can induce AO‐like atmospheric response (e.g., Butler et al, ; Nie et al, ). Variations of AO and WP are closely related to the change of sea ice (e.g., Linkin & Nigam, ; Overland et al, ) as well as the SST anomalies in extratropical and tropical oceans (e.g., Kwon et al, ; Xiao et al, ). The latter is suggested influence the TP snowfall by modulating the moisture supply as well (Yuan et al, , ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides the wave source, the teleconnection pattern also depends on the propagation of those Rossby waves. In extratropics, those waves triggered by tropical heating are always reinforced by nonlinear baroclinic eddy-mean flow feedbacks (Nie et al, 2014;Zhou et al, 2017) and atmospheric-ocean/land interactions (Fang & Yang, 2016;Xiao et al, 2016;Wang et al, 2019). A full understanding of the atmospheric response to tropical SST anomalies and the teleconnection pattern simulations must take into account the aggregate effects of the extratropical transient waves (Hoskins & Valdes, 1990) as well, which needs future investigations.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The occurrence of SSWs can be well explained by planetary wave forcing originating from the troposphere (Andrews et al, 1987; Matsuno, 1971). Although planetary waves are usually weaker in the Southern Hemisphere as compared with the Northern Hemisphere due to comparatively weak land‐sea thermal contrasts and smaller orography (e.g., Waugh & Polvani, 2010), they may occasionally amplify via atmospheric blocking, specific circulation patterns, or other atmospheric external forcing (e.g., Nie et al, 2013; Nishii et al, 2009; Nishii & Nakamura, 2004; Shen et al, 2020; Xiao et al, 2016). As a result, the upward propagation of planetary waves into the stratosphere can be enhanced via the linear interference between anomalous and climatological planetary waves, and the nonlinear instantaneous contributions from anomalous planetary waves (Nishii et al, 2009; Smith & Kushner, 2012).…”
Section: Introductionmentioning
confidence: 99%